MODERN ENGINEERING TECHNIQUES FOR THE PRODUCTION OF MODIFIED POLYSACHARIDES WITH BIOLOGICAL ACTIVITY (Innovation in Woodworking Industry and Engineering design, 2026)
Esters are used in the industry. The rapid increase in demand for esters in the food, cosmetics and pharmaceutical industries makes it mandatory to find alternative ways of synthesis instead of low-yield, expensive, energy-intensive and prolonged reactions. The production process for the synthesis of esters is based on chemical esterification of fatty acids with alcohol in the presence of inorganic catalysts at high temperatures. However, these chemical processes are non-selective and consume a large amount of energy. In this regard, the current situation of environmental degradation requires the development of efficient and environmentally friendly methods in terms of energy consumption and waste reduction. The synthesis of esters by sonication is also an economical and effective method of performing esterification with broad practical application. The article presents a review of research and modern engineering solutions based on "green technologies" for the synthesis of esters. Significant advantages of the method of transesterification of methyl caprate with sucrose, leading to esters with potential biological activity such as antifungal and antimicrobial agents, are highlighted.